2019
DOI: 10.20944/preprints201907.0250.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between Indoor Air Pollution and Acute Respiratory Infections among Under-Five Children in Afghanistan: Do SES and Sex Matter?

Abstract: Background: Low-income families often depend on fuels such as wood, coal, and animal dung for cooking. Such solid fuels are highly polluting and are a primary source of indoor air pollutants (IAP). We examined the association between solid fuel use (SFU) and acute respiratory infection (ARI) among under-five children in Afghanistan and the extent to which this association varies by socioeconomic status (SES) and gender. Materials and Methods: This is a cross-sectional study based on de-identified data from Afg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 26 publications
5
35
0
Order By: Relevance
“…Regarding child related risk factors associated with ARI, risk of having ARI is 26%, 34% and 51% less likely respectively among children of aged 2-3 years, 3-4 years and 4-5 years compared to children of below one year which suggests the exposure of children for cooking induced indoor air pollutants decreases with age. The nding complies with a prior study in urban areas of Oromia region, Ethiopia [36]; in Wondo-Genet district, southern Ethiopia [19] and in Afghanistan [37]. This could be because of the few time the older children spend with their mothers in the house [37], and the higher number in younger children could be associated with the underdeveloped epithelial linings of the lungs and weaker immune system of younger children compared with the older counterparts [37][38][39].…”
Section: Discussionsupporting
confidence: 88%
“…Regarding child related risk factors associated with ARI, risk of having ARI is 26%, 34% and 51% less likely respectively among children of aged 2-3 years, 3-4 years and 4-5 years compared to children of below one year which suggests the exposure of children for cooking induced indoor air pollutants decreases with age. The nding complies with a prior study in urban areas of Oromia region, Ethiopia [36]; in Wondo-Genet district, southern Ethiopia [19] and in Afghanistan [37]. This could be because of the few time the older children spend with their mothers in the house [37], and the higher number in younger children could be associated with the underdeveloped epithelial linings of the lungs and weaker immune system of younger children compared with the older counterparts [37][38][39].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies reported comparable results that SFU and exposure to IAP increase the risk of infant and child mortality in LMICs (17)(18)(19)(20)(21)(22). Evidence suggests that the combustion of SFU emits multiple pollutants such as fine particles, carbon monoxide, formaldehyde, and many more toxic chemicals, which increase the risk of mortality from ALRIs, asthma, and pneumonia among infant and young children exposed to these pollutants (3,6,7,(23)(24)(25)(26)(27)(28)(29). Exposure to these toxic pollutants also increases the risk of low birth weight, stillbirth, and preterm birth, including acute and chronic health problems, all of which are considered as leading causes of child mortality (20,22,30,31).…”
Section: Exposuresmentioning
confidence: 86%
“…Previous studies emphasized to consider cooking place along with SFU for examining the association between IAP and child-mortality because cooking inside the house with solid fuels maximizes the concentrations of airborne toxic pollutants in the household and ambient air (20,23,32,33). Following the previous study, we employed an inclusive SFU exposure measure combining both SFU and cooking place and found stronger associations of high exposure to IAP with infant and child mortality (23). Consistent with our study, previous studies showed that children were exposed to higher concentration of pollutants from SFU because of high proximity to pollutants and spending much time in the kitchen during heating and cooking, which intensifies the risk of child mortality from ALRI including other adverse health outcomes (17,23,24).…”
Section: Exposuresmentioning
confidence: 99%
See 2 more Smart Citations